IMPROVING STUDENTS’ ORAL HEALTH KNOWLEDGE THROUGH TIKTOK AT SMPN 1 KERTAK HANYAR: PENINGKATAN PENGETAHUAN KESEHATAN GIGI DAN MULUT SISWA SMPN 1 KERTAK HANYAR MELALUI TIKTOK - Hamdani, Riky; Setyawardhana, Raden Harry Dharmawan; Hatta, Isnur; Azizah, Aulia (Faculty of Vocational Studies, Universitas Airlangga, 2025)
Background: Oral health education plays a vital role in increasing public awareness and promoting healthy behaviors. TikTok, as an audiovisual platform, is considered effective because it is engaging, easy to use and share, stimulates creativity, increases participation, and enhances students’ digital skills. This approach is particularly relevant at SMPN 1 Kertak Hanyar, where most students have not yet developed proper oral hygiene habits or knowledge of correct toothbrushing practices, and the school has never conducted digital-based oral health education. Objective: This community service activity aimed to improve the oral health knowledge of students at SMPN 1 Kertak Hanyar. Method: The program was conducted in several stages, including coordination with the school, interactive oral health education sessions, the use of TikTok content as an educational medium, and mentoring activities. Evaluation was carried out through pre-tests and post-tests to measure students’ knowledge improvement. Results: The findings showed an increase in knowledge across all assessed indicators, with the highest improvement observed in the item regarding the appropriate amount of toothpaste to use (27.76%). The Wilcoxon test yielded a p-value of 0.000 (p < 0.05), indicating a significant difference in knowledge before and after the intervention. Conclusion: Health education through TikTok effectively improved students’ oral health knowledge. Therefore, social media, particularly TikTok, is recommended as a sustainable medium for oral health promotion.